Identification of multiple physicochemical and structural properties associated with soluble expression of eukaryotic proteins in cell-free bacterial extracts - Tokmakov, Alexander A. (Frontiers in Microbiology, 2014)
Bacterial extracts are widely used to synthesize recombinant proteins. The vast volume of data has been accumulated in cell-free expression databases, covering a whole range of existing proteins. It makes possible comprehensive bioinformatics analysis and identification of multiple features associated with protein solubility and aggregation. In the present paper, an approach to identify the multiple physicochemical and structural properties of amino acid sequences associated with soluble expression of eukaryotic proteins in cell-free bacterial extracts is presented. The method includes: 1) categorical assessment of expression data; 2) calculation and prediction of multiple properties of expressed sequences; 3) correlation of the individual properties with the expression scores; and 4) evaluation of statistical significance of the observed correlations. Using this method, a number of significant correlations between calculated and predicted properties of amino acid sequences and their propensity for soluble cell-free expression have been revealed.